Why Do Tougher Caseworkers Increase Employment? The Role of Program Assignment as a Causal Mechanism - Huber, Martin; Lechner, Michael; Mellace, Giovanni (The Review of Economics and Statistics, 2017)
Previous research found that less accommodating caseworkers are more successful in placing unemployed workers into employment. This paper explores the causal mechanisms behind this result using semi-parametric mediation analysis. Analyzing rich linked job seeker-caseworker data for Switzerland, we find that the positive employment effects of less accommodating caseworkers are not driven by a particularly effective mix of labor market programs but, rather, by other dimensions of the counseling process, possibly including threats of sanctions and pressure to accept jobs.